PROTOTIPE LORI INSPEKSI ELEKTRIK BERTENAGA SURYA (LORI PPI E-2000 GENERASI 3) - Atmaja, Dadang Sanjaya; Prasetya, Henry Widya (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2020)
The use of inspection lorries in infrastructure maintenance activities is needed to minimize labor in maintenance and time efficiency. The development of inspection lorries at the Indonesian Railroad Polytechnic of Madiun continues, starting from the motor, wheels, frames, body, rubber dumper and solar panels as the main energy source. The motor uses a BLDC (Brushless direct current) electric motor with a power of 2680 Watts, a current of 35 A and a rotating speed of 4250 Rpm which is environmentally friendly. The development of the inspection lorry uses a monoblock structure with a casting process. The material used comes from nodular cast iron (FCD), having an average hardness of 191 HB. Rubber dampers are known as shock absorbers with a length of 185 mm, a width of 60 mm, and a height of 30 mm. The composition of the Rubber damper material is as follows: 55% natural rubber, 25% Carbon black, 5% White oil, 3% Zine oxide, 2% Accelerator, 2% Anti Oxidant, 3% Steread Axid, and 5% sulfur. The inspection lorry body is made of fiber reinforced polymers of plastics (FRP) type composite material. This composite uses a polymer made from polyester resin as a matrix (binder) and strengthens fibrous glass fibers using the hand lay-up method. Solar panels are the main energy source to supply the electric motor power. Solar panels can work optimally with a Pmax presentation reaching 99.29% and a range of 11 km. The railroad geometry measuring device is equipped with a maxbotic sensor to detect rail road width, a gyroscope as a height difference detector and a KTR displacement sensor to detect rail wear. The design of the PPI Madiun electric inspection lorry has high aesthetic and ergonomic value.